Network analysis of the structure and change in the mini‐mental state examination: A nationally representative sample. (31st December 2021) - Rotstein, Anat
Abstract: Background: The structure of the Mini‐Mental state examination (MMSE) is inconsistent across factor analytic studies, and yet to be examined based on network analysis. The current study aims to identify the (I) cross‐sectional network structure and (II) longitudinal network changes of the MMSE. Method: The MMSE was administered to a nationally representative sample of older adults (age 50 and over) in Ireland twice over 4 years (2012–2013: N = 7207; 2016: N = 5715). Psychometric network analysis was computed at each time point to identify the structure, strength and magnitude of the network associations. Item clustering was examined, and modularity scores were computed to measure the overall strength of clustering. Centrality indices were used to identify the main aspects of the MMSE. Longitudinal differences between the networks were examined. Result: Cross‐sectionally, the MMSE network structure clustered into a single community with orientation items identified as most central. Longitudinally, the MMSE was time invariant regarding structure, centrality and magnitude of the positive associations between the items. The average magnitude of the negative associations increased over time [(t(65.15) = 3.78, p < 0.001; time 1: M = − 0.59, SD = 0.58 time 2: M = − 1.65, SD = 1.97] as did their percentage. Conclusion: Network analysis of the MMSE showed that the measure consisted of a single entity of cognitive functioning irrespective of time. Orientation items were repeatedly identified as most central. Longitudinal changes of the network were evident in increased negative associations between selected cognitive components after 4 years of follow‐up. These changes may be explained by neuro‐cognitive compensation processes.